The Relationship between Mother's Knowledge and Culture and Exclusive Breastfeeding in the Barambai Health Center Area Barito Kuala Regency in 2018 - Putri, Rosalina Dewi Ansari (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2023)
Some of the most common causes of exclusive breastfeeding failure are lack of mother's knowledge, lack of family support, socio-cultural factors, psychological factors, maternal physical factors, and a lack of health officerwho provide information on exclusive breastfeeding. The research method used an analytical survey with Cross Sectional approach. The population is mothers with babies> 6 months to 12 months, and 150 people as research samplesin the work Area of PuskesmasBarambai. Sampling technique is done by Accidental Sampling, and technique of data analysis using Chi square. The results of the study, from 150 respondents, mothers who gave exclusive breastfeeding only 10 people (7%), had good knowledgeonly 16 people (10,6%) and had good culture is 28 people (18,6%). The statistic test shows that there is a relation between knowledge and Exclusive breastfeeding, ρ = 0.001 (ρ <α = 0.05) and there is a relation between cultureand Exclusive breastfeeding, ρ = 0.003 (ρ <α = 0.005).